2017
DOI: 10.1016/j.ijinfomgt.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adoption of mobile banking by Jordanian bank customers: Extending UTAUT2 with trust

Abstract: Banks seem to be one of the most business that are really interested in such systems to provide their customers better services as well as to enhance their effectiveness and efficiency. However, the successful implementation of Mobile banking largely depends on the extent of how much customers are fully motivated to adopt it. In fact, over the Jordanian context, the adoption rate of mobile banking is very low and quite few studies that have examined the related issues of mobile banking. Thus, the purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

172
1,098
19
58

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,173 publications
(1,347 citation statements)
references
References 65 publications
(200 reference statements)
172
1,098
19
58
Order By: Relevance
“…The citizens are one of the most important stakeholders of such developments. Hence, in order to avoid resistance from stakeholders and failure of such initiatives Hughes et al 2016Hughes et al , 2017, the perceptions of citizens and government employees towards various aspects of smart cities should also be explored by utilising established theories and models (see for example, AlAlwan et al 2017;Dwivedi et al 2011aDwivedi et al , 2011bDwivedi et al , 2013Dwivedi et al , 2016Dwivedi et al , 2017bDwivedi et al , 2017cHossain and Dwivedi 2014;Kapoor et al 2014aKapoor et al , 2014bKapoor et al , 2015Rana and Dwivedi 2015;Rana et al 2015aRana et al , 2015bRana et al , 2016Rana et al , 2017Shareef et al 2011Shareef et al , 2016aShareef et al , 2016bShareef et al , 2017Sinha et al 2017;Slade et al 2015;Veeramootoo et al 2018;Weerakkody et al 2013Weerakkody et al , 2017) from information systems and electronic government domains.…”
Section: Limitations and Future Scopementioning
confidence: 99%
“…The citizens are one of the most important stakeholders of such developments. Hence, in order to avoid resistance from stakeholders and failure of such initiatives Hughes et al 2016Hughes et al , 2017, the perceptions of citizens and government employees towards various aspects of smart cities should also be explored by utilising established theories and models (see for example, AlAlwan et al 2017;Dwivedi et al 2011aDwivedi et al , 2011bDwivedi et al , 2013Dwivedi et al , 2016Dwivedi et al , 2017bDwivedi et al , 2017cHossain and Dwivedi 2014;Kapoor et al 2014aKapoor et al , 2014bKapoor et al , 2015Rana and Dwivedi 2015;Rana et al 2015aRana et al , 2015bRana et al , 2016Rana et al , 2017Shareef et al 2011Shareef et al , 2016aShareef et al , 2016bShareef et al , 2017Sinha et al 2017;Slade et al 2015;Veeramootoo et al 2018;Weerakkody et al 2013Weerakkody et al , 2017) from information systems and electronic government domains.…”
Section: Limitations and Future Scopementioning
confidence: 99%
“…The result shows the usefulness factor had a significant effect on millennial interest using e-money product. The more useful and beneficial, then interest using e-money product will rise [3,4,9,10] The result shows that ease of use had a significant effect on interest using e-money. Easiness of e-money product used has an effect on interest using e-money.…”
Section: Hypothesis Testmentioning
confidence: 97%
“…Somebody will be interested if the required facilities is available and easy to be found. Alalwan et al [10], supporting facilities factor had a significant effect on people interest using moblie banking while Oliveira [4] explained that supporting facilities had no significant effect on people interest using mobile payment. The difference results of research is the main reason of this research to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Alalwan et al, [7] examined the effective factors on acceptance of mobile banking by Jordan Bank customers. The results showed that mainly behavioral intention has positive and significant effect on performance expectations, expectation of effort, motivation, cost value and trust.…”
Section: Literature Review and Theoretical Framework Of The Studymentioning
confidence: 99%